Under the veil of captivity the metaphorical universe of Su Tong's Mahogany street series - Silva, Flavio (Perspective in the Arts and Humanities ASIA (formerly Asian Perspectives in the Arts and Humanities), 2021)
The metaphorical universe of Su Tong's Mahogany Street series is both profound and unsettling. It intimately resonates with some of the most relevant philosophical and sociopolitical issues in modern China, such as the Cultural Revolution's legacy, so-called historical amnesia, and the "identity crisis" that resulted from the Chinese economic reform in the late 1970s and early 1980s. Through its labyrinthine design, Su Tong ultimately depicts, in great depth, a particular condition of captivity-both subjective and objective - experienced by many characters in those works, which is presented as a consequence of Mahogany Street's abject reality and its oppressive and over-industrialized urban background. In my article, which draws on textual analysis as well as a personal interview with the author, I explore the implications of this "captivity" condition, in order to ground my claim that it resides at the essence of these works. I also argue that its metaphorical significance emerges as a compelling mimetic device that provides further insight into the plight endured by many Chinese mainland citizens from Cultural Revolution to post-Mao marketization days.